If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x+7=-14-6x
We simplify the equation to the form, which is simple to understand
-3x+7=-14-6x
We move all terms containing x to the left and all other terms to the right.
-3x+6x=-14-7
We simplify left and right side of the equation.
+3x=-21
We divide both sides of the equation by 3 to get x.
x=-7
| y=80x+900 | | 188=-2+4(6x-8) | | -3x+3=2x-12 | | 6(4x+5)=2x | | -1+6x=17 | | 14x-2x^2=x | | 3m+3=m-5 | | 13x-7x+5x=-11 | | 8=4(3c+3) | | -10v=60 | | 2t-2=-2 | | 3x-3=2x-12 | | 5v^2+6v+7=v^2-4v | | 3d-12=-3 | | 0.4w-11=-0.5w | | 6+n=28+9 | | 2x+27=5x-3 | | r=50x-200 | | 188=-2x+4(6x-8) | | -8-3n=1 | | a+6=98 | | 3x+8=7x-12 | | 3x-2=2x-2 | | 98=7x+3(4x-18) | | 4c-6=3 | | x^2+20x= | | 0=.75x+75 | | -10x-10=-6x-30 | | 13x-4=6x+24 | | -y-15+9y=3y+2+4y | | 3w-18w=-60 | | 14=-(-6-8) |